2002
DOI: 10.1210/jcem.87.3.8279
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ghrelin and of the GH Secretagogue Receptor by Pancreatic Islet Cells and Related Endocrine Tumors

Abstract: Ghrelin is a novel gastrointestinal hormone produced by rat and human gastric X-like neuroendocrine cells, which strongly stimulates GH secretion and influences energy balance, gastric motility, and acid secretion. Ghrelin is expressed in pituitary and gastrointestinal endocrine tumors. It binds to the GH secretagogue receptor (GHS-R), which is present in a wide variety of central and peripheral human tissues. The aim of the present study was 2-fold: 1) to determine, by immunohistochemistry and mRNA analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
160
2
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(176 citation statements)
references
References 55 publications
9
160
2
5
Order By: Relevance
“…Second, epsilon cells do not produce other pancreatic hormones (insulin, glucagon, somatostatin) at any time during development. Date et al [11] presented data indicating that ghrelin is co-localised with glucagon in adult human and rat pancreas, whereas results from Volante et al [12] indicated that ghrelin is co-localised with insulin in human. We were not able to confirm either of these results; instead, our data indicate that through to adult life ghrelin peptide production is confined to a distinct cell type [4,5,13,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, epsilon cells do not produce other pancreatic hormones (insulin, glucagon, somatostatin) at any time during development. Date et al [11] presented data indicating that ghrelin is co-localised with glucagon in adult human and rat pancreas, whereas results from Volante et al [12] indicated that ghrelin is co-localised with insulin in human. We were not able to confirm either of these results; instead, our data indicate that through to adult life ghrelin peptide production is confined to a distinct cell type [4,5,13,21].…”
Section: Discussionmentioning
confidence: 99%
“…The origin of epsilon cells in the rodent and human pancreas remains controversial. Ghrelin has variably been reported to be present in alpha cells in rats and humans [11], in beta cells in humans [12] or in separate cell types [4,13,14]. In human and rodent pancreases of neonates and adults, a few epsilon cells remain visible in marginal areas of the islets [4,5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Limited evidence for the role of CST in tumour growth control has already been reported [16,17]. Since all immunohistochemically CST-positive tumours did not contain MrgX2 protein, whereas the expression of SRIF receptors (particularly SRIF receptors 2, 3, and 5) and/or GHSR-1a had previously been detected [20][21][22][23][24] in all samples (at either protein or mRNA level), the actions of CST were probably mediated by pathways other than CST/MrgX2 in the tumours investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The SRIF receptors and GHS-R1a status of most cases of the current neuroendocrine tumour series have been reported previously [20][21][22][23][24]. Additional RT-PCR experiments for SRIF receptors and GHS-R1a were also performed in selected cases, with special reference to non-tumour and neoplastic parathyroid tissue, according to previously published protocols [20,21].…”
Section: Molecular Analysis Of Cst and Mrgx2 Transcriptsmentioning
confidence: 99%
See 1 more Smart Citation